Best Practices Pengelolaan Layanan Otak dan Saraf sebagai Core Business di RSOMH Bukittinggi - Susi Masfar; Delfia Tanjung Sari (Jurnal Mirai Management, 2023)
This study aims to identify best practices in the management of neurology and neurosurgery services at RSOMH Bukittinggi, involving informants from both management and medical specialist categories. The research was conducted through a series of in-depth interviews with seven informants divided into two categories. The questions asked covered their views on the core business, challenges faced, and concrete steps taken by the hospital to enhance neurology and neurosurgery services. From the interviews, best practices in the management of neurology and neurosurgery services at RSOMH Bukittinggi were identified. Firstly, optimizing health tourism services with a focus on the hospital's core business. Secondly, implementing a Stroke Check Up program for prevention and early detection. Thirdly, collaborating with the Faculty of Medicine at the University of Indonesia for knowledge and technology development. The results of this study provide insights into best practices that other hospitals can adopt in managing neurology and neurosurgery services. Optimization of the core business focus and prevention programs can enhance the hospital's reputation and attractiveness. Collaboration with reputable medical institutions also holds the potential to improve service quality and human resource development. These implications can assist RSOMH Bukittinggi in achieving its vision and mission as a high-quality and innovative center for neurology and neurosurgery services. Keywords: Best Practice, Management, RSOMH Bukittinggi, Core Business